Band gap tuning and optical properties of BiFeO3 nanoparticles. (2020) - Sharma, Sheetal; Kumar, Manoj
Abstract: BiFeO3 nanoparticles prepared by using sol-gel technique and sintering at different temperatures (500 °C, 600 °C and 700 °C) have been studied. The influence of different sintered temperature on crystal structure and energy band gap of BiFeO3 samples has been investigated. X-ray diffraction results exhibit distorted rhombohedral structure of BiFeO3 samples. However, a small fraction of impurity phase has been observed for sample sintered at 700 °C and therefore, sintering temperature of 600 °C has been found suitable to obtain phase pure BiFeO3 sample. From XRD analysis it has been observed that crystallite size increases from 18 nm to 43 nm with rise in sintering temperature. The presence of various Fe-O and Bi-O bands has been confirmed from infrared spectroscopy. UV–Visible spectroscopy measurements show the variation in optical band gap from 2.5 eV to 2.0 eV with increasing sintering temperature from 500 °C to 700 °C for BiFeO3 samples indicating the tuning of optical band gap of BiFeO3 system in visible region.